ONLINE MOTORCYCLE TAXIS BOOST CULINARY BUSINESS ON MICRO SMALL AND MEDIUM ENTERPRISES - Maiercherinra Daud; Feralando Rama Kusuma Densis; Bertha Beloan (Jurnal RAK (Riset Akuntansi Keuangan), 2022)
The purpose of this study was to determine the impact of the presence of online motorcycle taxis on MSME business such as Dionza stall. The research method used is a qualitative method through a phenomenological approach. The result of this study indicate that the role of online motorcycle taxis is very helpful for Dionza Stall, especially during the covid-19 pandemic. The impact given, apart from increasing income, also helps customers who have limited time to come directly to the stall. It can be evidenced by an increase in income of approximately 30% every day. Keywords: Online Motorcycle, Culinary, Small and Medium Business